Masyarakat Ideal Dalam Pandangan Said Nursi - Nur Kholis (Journal Khafi : Journal Of Islamic Studies, 2023)
Musyarakah as a product based on partnership, if it is to be successful, its implementation must rely on fair competition and prevent abuse of a dominant position in business partnerships, and the most important thing is to overcome any problems related to agreements based on musyarakah contracts based on the principle of justice. This is where the principle of justice plays an important role, especially in standard contracts made by the parties in it. This justice is the most important value that must be reflected in the contract, so as to create an ideal social order.Related to the problems above, the writer feels the need to examine the thoughts of a figure who comes from Turkey. His name was Said Nursi and the title Badi'uzzaman. He is a well-known figure with his zuhud attitude. A charismatic Sufi. Besides that, he is also a thinker of the XX century. The ideas or thoughts are quite brilliant. Such as regarding the order of harmonious relations between religions so as to create a dream-like situation. A situation where people can respect each other, interact well and harmoniously, regardless of the differences that eventually lead to the outbreak of conflict.